Case Report: Temporary pacing using active fixation lead and invasive electrophysiology studies for immune checkpoint inhibitor associated reversible advanced atrioventricular block - Wang, Yifan; Qian, Min; Jin, Xiaofeng; Wang, Jiaqi; Chen, Taibo; Gao, Peng; Cheng, Zhongwei; Lai, Jinzhi; Liu, Yongtai; Fan, Jingbo; Zhang, Lihua; Cheng, Kangan; et al. (Frontiers in Cardiovascular Medicine, 2024)
A case of immune checkpoint inhibitors (ICIs)-associated myocarditis with reversible advanced atrioventricular block (AVB) was reported. We innovatively used active fixation lead connected to an external device for prolonged temporary pacing until atrioventricular conduction recovered. Invasive electrophysiology studies were performed to evaluate atrioventricular conduction in detail. Long-term follow-up for nearly 120-days and repeated long-term electrocardiography was conducted to ensure the conduction system was truly recovered.